Beyond academia: a reflexive exploration of a professor’s journey from awareness to advocacy of the African American studies course curriculum - Scott, Lawrence (Frontiers in Education, 2023)
In 2020, African American Studies course was unanimously passed as an elective course for high school credit in Texas. Since that time, the course has been met with societal and legislative resistance, due to the ubiquity of anti-Critical Race Theory laws around the nation. This submission seeks to understand the lived experience of a university professor, who minored in History, taught Social Studies in predominantly Black and Brown communities, but discovered the vast absence of African American contributions in the high school and higher education curricula. It was when he led a national advisory team for the Texas State Board of Education that helped revise, pass, and implement the African American Studies course for a high school credit, that he realized how vital this course is for all students. This reflexive narrative account seeks to understand the process of the author's transition from an interested educator aware of Black History to an avid advocate with full appreciation of a comprehensive African American Studies course for high school students.